Módulo de didáctica general aplicada a la educación intercultural bilingüe - Paca Caguana, María Juana (2001)
Introduction. Overview of teaching. Educational trends. Learning objective. Educational experiences - teaching of bilingual intercultural education in Ecuador. Proposal dela teaching methodology - didactics of intercultural bilingual education. Bibliography. Annexed. Glossary.